ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9413530
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Transferred Representations for Stock Classification

Abstract: Stock classification is a challenging task due to high levels of noise and volatility of stocks returns. In this paper we show that using transfer learning can help with this task, by pre-training a model to extract universal features on the full universe of stocks of the S&P500 index and then transferring it to another model to directly learn a trading rule. Transferred models present more than double the risk-adjusted returns than their counterparts trained from zero.In addition, we propose the use of data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Indeed, it has extensively been shown that, in financial applications, deep learning (DL) models are often capable of outperforming traditional approaches due to their ability to learn complex data representations based on end-to-end data-driven training, see, e.g., [19][20][21][22][23][24]. DL models have been adopted for a variety of problems ranging from price prediction [25][26][27][28][29], limitorder book-based mid-price prediction [20,21,23,30,31], and volatility prediction [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has extensively been shown that, in financial applications, deep learning (DL) models are often capable of outperforming traditional approaches due to their ability to learn complex data representations based on end-to-end data-driven training, see, e.g., [19][20][21][22][23][24]. DL models have been adopted for a variety of problems ranging from price prediction [25][26][27][28][29], limitorder book-based mid-price prediction [20,21,23,30,31], and volatility prediction [32][33][34].…”
Section: Introductionmentioning
confidence: 99%